Conceptual Framework of Fiduciary Risks - Khanal, Gopi Krishna (Prashasan: The Nepalese Journal of Public Administration, 2022)
Nepal has adopted a course of federal governance by transferring expenditure and revenue functions to sub-national government in the form of fiscal federalism. Nevertheless, in recent years, fiduciary risks have been frequently discussed topics in fiscal federalism. This article provides some conceptual framework of fiduciary risks with particular focus on local finance. This descripto-analytical article briefly examines the relationship between the level of fiscal decentralization and fiduciary risks at local government as well. Despite some methodological limitations of cross-sectional regression analysis, it is found that the level of fiscal decentralization is associate with fiduciary risks. This provides some hints for precaution. Government of Nepal should help local government to improve their level of fiduciary governance.